Research on inertia transfer in load simulation of tracked vehicle under complex working conditions - Lv, Gang; Lv, Haoliang; Chen, Zhaomeng; Chu, Wei; Mao, Jiliang (Frontiers in Materials, 2023)
At present, research on the loading simulation test bench for overloaded vehicles is mostly limited to the realization of loading simulation under the condition of straight line driving of the vehicle. When simulating the whole vehicle load under straight line driving condition, only accurate road load and inertial load can be obtained to achieve accurate load simulation, and the inertial load required to be simulated by each side device is half of the whole vehicle inertial load. However, straight line driving is only the most ideal driving. The real driving conditions (including ground conditions) of the vehicle are usually composed of steering, longitudinal slope, lateral slope and different ground adhesion coefficients. Therefore, the loads borne by the two independent load simulation systems located on both sides of the vehicle may be different during the load simulation process. In addition, the frequency characteristics of the loads to be simulated by the same side load simulation device at different time sequences may also be different. This paper studies the dynamics modeling, load distribution and error compensation in the whole vehicle load simulation process in order to achieve accurate crawler vehicle load simulation from three aspects.